Análise técnica e econômica de propriedades rurais do município Independência - estado do Ceará - Bezerra, Luiz Júlio Farias (2011)
The present work aims to make the main technical and economic analysis of farms in the municipality of Ceará of Independence, with the objective of the study activities of cattle and sheep-goat. The data used for analysis of these farms and their activities were obtained through questionnaires and then tabulated to identify technological index, balance sheet and the application of measures of economic output for the year 2009. It was concluded that the farms have low technological level due to the low use of improved practices. The assets and liabilities in respect of farms increases the levels of technology used in the farms. As for measures of economic performance, rural properties showed favorable results for measures of liquidity, solvency and efficiency, but showed residual measures for infeasibility. In a global analysis, one can conclude that the farms have economic and financial viability, but present themselves as disabled the use of technology in management practices. The sheep-goat farm has a good use of improved practices, which allows the classification of the properties in rural technology levels above the average of the survey.